Mining urban sustainable performance: Spatio-temporal emission potential changes of urban transit buses in post-COVID-19 future. (15th December 2020) - Sui, Yi; Zhang, Haoran; Shang, Wenlong; Sun, Rencheng; Wang, Changying; Ji, Jun; Song, Xuan; Shao, Fengjing
Highlights: Proposing a framework to analyze emission patterns of buses and changes in post-COVID-19. 2056 buses with 1.5 million ridership and 7589 taxis with 0.2 million trips are used for analysis. 224 social surveys are collected and show a 56.3% ridership reduction in post-COVID-19. We find buses cannot be "greener" travel modal than cars if ridership reduces by more than 40%. Abstract: Emission benefits of transit buses depend on ridership. Declines in ridership caused by COVID-19 leads uncertainty about the emission reduction capacity of buses. This paper provides a method framework for analyzing spatio-temporal emission patterns of buses in combination with real-time ridership and potential emission changes in the post-COVID-19 future. Based on GPS trajectory and Smart Card data of 2056 buses from 278 routes covering 1.5 million ridership in Qingdao, China, spatio-temporal emissions characteristics of buses are studied. 7589 taxis with 0.2 million passengers' trips are used for acquiring private cars' emissions to evaluate the emissions difference between buses and cars. Empirical results show that the average difference between buses and cars with 2 persons can reach up to 117 g/km-person during 7:00–8:59 and 115 g/km-person during 17:00–18:59. However, buses have various emission benefits around the city at different periods. A double increase in emissions during non-rush hours can be observed compared with rush hours. 224 online survey data are used to study the potential ridership reduction trend in post-COVID-19. Results show that 56.3% of respondents would decrease the usage of buses in the post-COVID-19 future. Based on this figure, our analysis shows that per kilometer-person emissions of buses are higher than cars during non-rush hours, however, still lower than cars during rush hours. We conclude that when ridership reduces by more than 40%, buses cannot be "greener" travel modal than cars as before. Finally, several feasible policies are suggested for this potential challenge. Our study provides convincing evidence for understanding the emission patterns of buses, to support better buses investment decisions and promotion on eco-friendly public transport service in the post-COVID-19 future.